PERAN KONSELING INDIVIDU BEHAVIORISTIK TERHADAP KEDISIPLINAN SISWA DI SMP PANDANARAN PLUPUH TAHUN PELAJARAN 2021/2022 - Khasanah, Kismiyati (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
Abstract: The purpose of this study was to determine the role of behavioristic individual counseling on student discipline at SMP Pandanaran Plupuh in 2021/2022 academic year. This research was conducted at SMP Pandanaran Plupuh with a qualitative research paradigm. The method of data collection is through interview and observation techniques. The observation technique aimed to find out directly about the effectiveness of behavioristic individual counseling to overcome student discipline, the interview was to find out the background of the cause of indiscipline and how far the results of individual counseling services with behavioristic techniques have been applied. In this study, the research subject was Ryan Pramudya, a student in class VII at SMP Pandanaran Plupuh. The validity of the data was through source triangulation techniques and technical triangulation techniques. Meanwhile, to analyze the data, qualitative descriptive was used through steps such as data collection, data reduction, data display, and drawing conclusions. Based on the result of observation and interviews, it could be seen that after being given behavioristic individual counseling services for three weeks or three times providing services, there was a change for the better in students. This was evidenced by the attitude of a student who was more disciplined at school and more orderly in accordance with the conditions at school, and could maintain trust, control emotions, and was not easily offended. Key Words: Behavioristic Individual Counseling Techniquess, Student Discipline. Abstrak: Penelitian ini bertujuan Untuk Mengetahui Peran Konseling Individu Behavioristik Terhadap Kedisiplinan Siswa Di Smp Pandanaran Plupuh Tahun Pelajaran 2021/2022”. Penelitian ini dilaksanakan di SMP Pandanaran Plupuh, dengan paradigma penelitian kualitatif. Metode pengumpulan data yang digunakan adalah teknik wawancara dan observasi. Teknik observasi bertujuan untuk mengetahui secara langsung efektivitas konseling individu behavioristik untuk mengatasi kedisiplinan siswa; wawancara untuk mengetahui latar belakang penyebab dan seberapa jauh hasil pemberian layanan konseling individu dengan teknik behavioristik yang telah di terapkan. Dalam penelitian ini yang menjadi subyek adalah Ryan Pramudya siswa kelas VII di SMP Pandanaran Plupuh. Keabsahan data yang di gunakan adalah teknik triangulasi sumber dan teknik triangulasi teknik, sedangkan untuk menganalisis datanya digunakan diskriptif kualitatif dengan langkah- langkah pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan hasil observasi dan wawancara dapat diketahui bahwa siswa setelah diberikan layanan konseling individu behavioristik selama tiga minggu atau tiga kali pemberian layanan, ada perubahan ke arah yang lebih baik, terbukti dengan lebih disiplinnya siswa tersebut di sekolah dan lebih tertib sesuai keadaan yang ada disekolah, serta bisa menjaga amanah, bisa mengendalikan emosi dan tidak mudah tersinggung. Kata kunci :Teknik Konseling Individu Behavioristik, Kedisiplinan Siswa.